OPTIMIZING THE IMPLEMENTATION OF THE ONLINE POPULATION ADMINISTRATION INFORMATION SYSTEM (SIAK) IN BARRU REGENCY: CHALLENGES AND SOLUTIONS - Rosdiana; Wahyul AZ (Meraja journal, 2024)
[Full Paper] to pdf Copyright (c) 2024 Meraja journal